2017
DOI: 10.1016/j.jff.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry as a source of bioactive compounds for the treatment of obesity, type 2 diabetes and chronic inflammation

Abstract: Recent experimental and clinical studies suggest that consumption of blueberry products has potential health benefits in ameliorating the development of obesity and its related comorbidities, including type 2 diabetes (T2D) and chronic inflammation. Blueberry fruits are enriched with numerous bioactive components such as vitamins, phenolic acid and anthocyanins which could contribute to these protective effects. Possible mechanisms by which blueberries exert their beneficial properties include counteracting ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 127 publications
(228 reference statements)
1
93
0
3
Order By: Relevance
“…Epidemiological studies, together with animal and clinical research, suggest that blueberry fruit intake is associated with health benefits related to improved endothelial and vascular functions . Acute (<24 h) and chronic (6–8 weeks) intake of blueberries have been shown to benefit endothelial function, evaluated as improved brachial flow‐mediated dilation or peripheral arterial tone in healthy adults .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological studies, together with animal and clinical research, suggest that blueberry fruit intake is associated with health benefits related to improved endothelial and vascular functions . Acute (<24 h) and chronic (6–8 weeks) intake of blueberries have been shown to benefit endothelial function, evaluated as improved brachial flow‐mediated dilation or peripheral arterial tone in healthy adults .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, blueberry intake may confer health benefits for people with metabolic syndrome, prehypertension, or stage I hypertension . Blueberries contain many potentially bioactive compounds and nutrients including polyphenols, that could contribute to their health‐promoting properties . Blueberry polyphenols, and in particular the anthocyanins, are known to be extensively metabolized, with phenolic acids being identified as one of the most abundant classes of metabolites, with varying levels and duration in the circulation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, berry FP, particularly from cranberry ( Vaccinium macrocarpon ) and blueberry ( Vaccinium corymbosum ), has high levels of phenolics (Li, Feng, Huang, & An, ; Mildner‐Szkudlarz et al., ) and dietary fibers (DFs) (Gouw, Jung, & Zhao, ). Several studies have reported the potential anticancer, antioxidant, and antimicrobial properties of blueberry pomace (BP) and cranberry pomace (CP) (Das, Islam, Marcone, Warriner, & Diarra, ; Huang, Zhang, Liu, & Li, ; Rupasinghe, Neir, & Parmar, ; Shi, Loftus, McAinch, & Su, ). Berry FPs also retain a significant amount of color, aroma, and flavor compounds, and can therefore provide desirable sensory attributes to food products.…”
Section: Introductionmentioning
confidence: 99%